2011
DOI: 10.1002/asi.21482
|View full text |Cite
|
Sign up to set email alerts
|

Toward video semantic search based on a structured folksonomy

Abstract: This study investigated the effectiveness of query expansion using synonymous and co-occurrence tags in users' video searches as well as the effect of visual storyboard surrogates on users' relevance judgments when browsing videos. To do so, we designed a structured folksonomy-based system in which tag queries can be expanded via synonyms or co-occurrence words, based on the use of WordNet 2.1 synonyms and Flickr's related tags. To evaluate the structured folksonomy-based system, we conducted an experiment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…In social summarization, video tags known to be similar to or better than indexer‐assigned terms (Heckner, Neubauer, & Wolff, ; Kim, ) can be effectively used as key concepts to select significant sentences from speech transcripts. Heckner et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In social summarization, video tags known to be similar to or better than indexer‐assigned terms (Heckner, Neubauer, & Wolff, ; Kim, ) can be effectively used as key concepts to select significant sentences from speech transcripts. Heckner et al.…”
Section: Introductionmentioning
confidence: 99%
“…() claim that videos on YouTube are extensively tagged because uploaders want their videos to be retrieved and viewed by as many people as possible, and not because they want to organize their personal collection. Similarly, Kim () notes that video tags seem to be closer to indexer‐assigned terms than image tags because YouTube videos have a proportionally greater number of tags describing video content than Flickr images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use Flickr because some words, such as proper nouns and new words that are included in video tags, are not defined in WordNet but can be found in Flickr tags. We assume that our proposed method is closely related to named entity extraction because it was observed that frequently assigned video tags are related to named entities, such as people and object categories (Kim, 2011). Further, we also expect that the semantic relations between tags can be effectively utilized for extracting key sentences from a document.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Heckner, Neubauer, and Wolff (2008) stated that videos on YouTube are extensively tagged because users want their videos to be retrieved and viewed by as many people as possible and not because they want to organize their personal collections. Similarly, Kim (2011) suggested that video tags are similar to indexer‐assigned terms and valuable in describing objects or people in a video, since the most frequently employed categories are topics, objects, metadata elements, and people.…”
Section: Introduction and Related Studiesmentioning
confidence: 99%